IN SITU MONITORING OF A CONTROLLED RELEASE OF FERTILIZERS IN LETTUCE CROP - Claudinei F. Souza; Roselena Faez; Fabiana B. Bacalhau; Murilo F. Bacarin; Tamires S. Pereira (Engenharia Agrícola, 2017)
ABSTRACT: Agriculture has sought ways to increase food production to meet global demands, intensifying dependence on natural resources. An alternative for intensive production has relied on the use of “smart” fertilizers that release nutrients in a controlled manner. Biodegradable polymers containing fertilizers has presented economic and environmental advantages when applied to the soil, as they release water and nutrients gradually to the environment without leaving residues. The objective of this study was to monitor the behavior of chitosan-clay hybrid microspheres, used as potassium nitrate soil ferti-releaser in lettuce cultivation. The experiment consisted of two treatments: (i) application of ferti-releasing chitosan-clay microspheres and (ii) use of conventional fertilization. Both treatments were monitored with TDR probes to measure electrical conductivity and soil moisture. The results indicate that both moisture and electrical conductivity are higher in soils treated with the ferti-releasing material. In addition, there was a gradual and homogenous release if compared to the conventional fertilization. The statistical analysis showed that the microspheres were efficient mainly for the controlled nitrogen release.